Sistem Informasi Sumber Daya Manusia Pada Perguruan Tinggi - Didik Nugroho Tri Irawati (STMIK Sinar Nusantara, 2007)
Information system of human resource, there is very important for organization. University as an organization must manage their human resource, so the manager can made good decision. With HIPO, DFD, Database and form input and output then code with program language, it will get a software information system of human resource the software can used to made good decisionKeyword : system, information system